KEBIJAKAN STRATEJIK UNTUK MENINGKATKAN KETAHANAN SOSIAL DI TENGAH PANDEMI COVID-19 (STUDI KASUS INDEKS DESA MEMBANGUN PROVINSI KEPULAUAN BANGKA BELITUNG TAHUN 2018-2020): Strategic Policies to Increase Social Resilience in the Middle of the Covid-19 Pandemic - Fitriansyah; Atma Elfahdi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
A village's social resilience can be seen from the Social Resilience Index as measured by the Village Development Index. This study aims to analyze how much is the contribution measurement dimensions of the Social Resilience Index on the Value of the Social Resilience Index of the Bangka Belitung Islands Province in 2020 and to determine policies to increase social resilience in the Province of the Bangka Belitung Islands. Data analysis uses descriptive analysis with a quantitative approach that uses the twoway ANOVA method, linear regression analysis, SWOT analysis, and strategy evaluation. Primary data was obtained from the Village Development Index measurements for 2018-2020, RPJMD 2017-2022, and RKPD in 2020 for the Province of the Bangka Belitung Islands and supported by the results of interviews with stakeholders.. The results showed that East Belitung Regency had the highest Social Resilience Index during the 2018-2020 period compared to other districts/provinces. The compiler of the Social Resilience Index which consists of 4 (four) dimensions either jointly or partially contributethe Social Resilience Index and social capital is the dimension with the largest contribution (40.82%). The policy to increase social resilience in the Bangka Belitung Islands Province prioritizes the aid budget at locus/village which allocates the budget for the maintenance of infrastructure assistance, development, and supervision of social assistance. Further research is needed to determine the contribution of implementing these policies on increasing social security in the following year.